Artery encasement on preoperative CT scan does not preclude radical surgery: a case report utilizing sub-adventitial divestment for artery-involving pancreatic cancer. Issue 3 (11th October 2022) - Cai, Baobao; Lu, Zipeng; Miao, Yi
Abstract : Pancreatic cancer was most lethal malignancy and artery involvement was the most common clinic scenario that hindered radical resection for non-metastatic lesions. While artery resection and reconstruction combined pancreatectomies were significantly complicated, artery-sparing techniques were of interest. A patient was reported with pancreatic cancer encasing major abdominal arteries. Sub-adventitial divestment technique was performed to achieve curative-intend resection, indicating that artery encasement did not preclude radical surgery. Surgical maneuver as well as the rationale of this technique were presented and discussed in detail. In conclusion, technical resectability of artery-involving pancreatic cancer was determined by invasion depth of the lesion to tumor rather than the involving circumference. Surgical innovations were to increase the chance of curative resection.